Spatiotemporal brain mapping of spatial attention effects on pattern-reversal ERPs - Di Russo, Francesco; Stella, Alessandra; Spitoni, Grazia; Strappini, Francesca; Sdoia, Stefano; Galati, Gaspare; Hillyard, Steven A.; Spinelli, Donatella; Pitzalis, Sabrina (Human brain mapping, 2012)
Recordings of event‐related potentials (ERPs) were combined with structural and functional magnetic resonance imaging (fMRI) to investigate the timing and localization of stimulus selection processes during visual‐spatial attention to pattern‐reversing gratings. Pattern reversals were presented in random order to the left and right visual fields at a rapid rate, while subjects attended to the reversals in one field at a time. On separate runs, stimuli were presented in the upper and lower visual quadrants. The earliest ERP component (C1, peaking at around 80 ms), which inverted in polarity for upper versus lower field stimuli and was localized in or near visual area V1, was not modulated by attention. In the latency range 80–250 ms, multiple components were elicited that were increased in amplitude by attention and were colocalized with fMRI activations in specific visual cortical areas. The principal anatomical sources of these attention‐sensitive components were localized by fMRI‐seeded dipole modeling as follows: P1 (ca. 100 ms—source in motion‐sensitive area MT+), C2 (ca. 130 ms—same source as C1), N1a (ca. 145 ms—source in horizontal intraparietal sulcus), N1b (ca. 165 ms—source in fusiform gyrus, area V4/V8), N1c (ca. 180 ms—source in posterior intraparietal sulcus, area V3A), and P2 (ca. 220 ms—multiple sources, including parieto‐occipital sulcus, area V6). These results support the hypothesis that spatial attention acts to amplify both feed‐forward and feedback signals in multiple visual areas of both the dorsal and ventral streams of processing. Hum Brain Mapp, 2011. © 2011 Wiley‐Liss, Inc.